Long Noncoding RNA RAET1K Enhances CCNE1 Expression and Cell Cycle Arrest of Lung Adenocarcinoma Cell by Sponging miRNA-135a-5p - Zheng, Chang; Li, Xuelian; Ren, Yangwu; Yin, Zhihua; Zhou, Baosen (Frontiers in Genetics, 2020)
Molecular dysregulation is believed to participate in the onset and progression of lung adenocarcinoma (LUAD). This study aimed to identify and evaluate the potential key long noncoding RNAs (lncRNAs) involved in the significant dysfunctional process of LUAD. We found that lncRNA retinoic acid early transcript 1K (RAET1K) was upregulated in tumor tissues and were correlated with a poor prognosis of patients with LUAD; further, for the first time, we detected the biological roles of RAET1K. Weighted gene correlation network and gene set enrichment analysis revealed that high RAET1K expression is related to cell cycle dysfunction through upregulated cyclin E1 (CCNE1) by targeting miR-135. The dual-luciferase reporter gene assay was performed to clarify the binding relationship between RAET1K and miR-135a-5p in transgenic A549 and H1299 cells. Real-time PCR and Western blot analyses showed that RAET1K overexpression and miR-135a-5p inhibition exerted a strong synergistic effect on CCNE1 expression, and cell cycle flow cytometry analysis was used to confirm the arrest of A549 and H1299 cells at the G1/S phase. The lncRNA RAET1K/miR-135a-5p axis might participate in the regulation of LUAD progression by influencing CCNE1 expression and the accumulation of cells arrested at the G1/S phase boundary.